Strengthening Local Governance : Defining the Role of Upazila and Union Parishads - World Bank (Washington, DC, 2013)
This note focuses on the rural sector. It takes as its starting point the premise that the Upazila and the Union Parishads can jointly form the backbone of a system of rural local governments in Bangladesh. The key interventions required are to strengthen the Upazila as an independent tier of government - especially relative to national parliament - and to clarify the relationship between the Upazilas and Union Parishads so that the two can jointly work as one system of local government. In this context, holding elections at Upazila level will be an important step to take, but this action alone will not result in a sustainable or effective system of local governance. Upazilas require clarity on their functions and their relations to Union Parishads, adequate untied resources for which they can be held accountable and appropriate checks and balances on their powers. There is a broad social consensus for strengthening local governance in Bangladesh. This is largely expressed as support for strengthening the role of Upazila and Union Parishads, through elections and greater political decentralization.